Conversion of soy molasses, soy solubles, and dried soybean carbohydrates into ethanol - Long, Craig C.; Gibbons, William R. (International Journal of Agricultural and Biological Engineering, 2013)
Soy molasses and soy solubles are byproducts of the conventional soy protein concentrate and soy protein isolate manufacturing processes, respectively. Conversion of the carbohydrates in these byproducts into ethanol was examined. Standardized amounts of commercial cellulase enzymes (Novozyme cellulase,